A Realtime Voice Controlled Wheelchair for Specially Abled People - Dr. K. Sravan Kumar, Pamanji Deepika, Mahamad Farzana, Ojja Kaveri, Kumari Preethi, Pemmaraju Bharati Sai Sailaja (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
This abstract presents a novel solution for physically challenged individuals, specifically those who rely on wheelchairs for mobility. The proposed solution involves the development of a voice-controlled real-time wheelchair system, which is complemented by a mobile application. The system utilizes the HC-05 Bluetooth module, an Arduino UNO microcontroller, high torque DC motors, a 20A motor driver circuit, and a 12V, 7Amp battery. The objective of this project is to enhance the mobility and independence of physically challenged individuals by providing them with an easy-to-use and efficient wheelchair control mechanism. The system aims to provide enhanced control and convenience to users, enabling them to operate their wheelchairs more effectively and efficiently. The wheelchair system utilizes Bluetooth technology to establish a wireless connection between the wheelchair and a mobile device, such as a smartphone or tablet. This connection allows users to control the wheelchair's movements remotely, eliminating the need for physical contact with the wheelchair controls. The mobile application serves as the user interface, providing intuitive and customizable controls that cater to individual user needs and preferences